KARAKTERISTIK SISTEM HYBRID PLTS DAN TURBIN ANGIN HAWT SEBAGAI PEMBANGKIT LISTRIK - Jaya, Harie Setiyadi; Perkasa, Petrisly; Darung, Untung; Sukardi, Sukardi; Rahmat, Muhammad Hudan (Steam Engineering, 2025)
The energy crisis in the coastal areas of Central Kalimantan demands a power generation solution that is independent, reliable, and easily transported. This study aims to develop and test the performance of a portable Hybrid Power Plant (PLTH) prototype that combines solar panels and a Horizontal Axis Wind Turbine (HAWT). The method used is experimental research, including the design, fabrication, and performance testing of the prototype directly in the field. Voltage output measurements were carried out on both energy sources to validate the system's performance under varying weather conditions. The test results show that the prototype successfully operates effectively, where the solar panels produce a peak voltage of 20V in sunny weather and the wind turbine reaches 24V at a speed of 360 rpm. The successful integration of these two sources proves the advantages of a complementary hybrid system, while offering a portable energy solution applicable to remote areas